2022
DOI: 10.1038/s41467-022-31098-6
|View full text |Cite
|
Sign up to set email alerts
|

NUP62 localizes to ALS/FTLD pathological assemblies and contributes to TDP-43 insolubility

Abstract: A G4C2 hexanucleotide repeat expansion in the C9orf72 gene is the most common genetic cause of ALS and FTLD (C9-ALS/FTLD) with cytoplasmic TDP-43 inclusions observed in regions of neurodegeneration. The accumulation of repetitive RNAs and dipeptide repeat protein (DPR) are two proposed mechanisms of toxicity in C9-ALS/FTLD and linked to impaired nucleocytoplasmic transport. Nucleocytoplasmic transport is regulated by the phenylalanine-glycine nucleoporins (FG nups) that comprise the nuclear pore complex (NPC) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 135 publications
4
39
0
Order By: Relevance
“…Nup98 is highly cohesive due to its extreme hydrophobicity and interacts with Nups from multiple subcomplexes (Griffis et al, 2003; Onischenko et al, 2017; Yoshida et al, 2011); therefore Nup98 may be uniquely capable of seeding toxic condensates. Our findings are consistent with recent studies reporting that cytoplasmic FG-Nups drive aggregation of TDP-43 in both ALS/FTLD and following traumatic brain injury (Anderson et al, 2021; Gleixner et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nup98 is highly cohesive due to its extreme hydrophobicity and interacts with Nups from multiple subcomplexes (Griffis et al, 2003; Onischenko et al, 2017; Yoshida et al, 2011); therefore Nup98 may be uniquely capable of seeding toxic condensates. Our findings are consistent with recent studies reporting that cytoplasmic FG-Nups drive aggregation of TDP-43 in both ALS/FTLD and following traumatic brain injury (Anderson et al, 2021; Gleixner et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with recent studies reporting that cytoplasmic FG-Nups drive aggregation of TDP-43 in both ALS/FTLD and following traumatic brain injury (Anderson et al, 2021;Gleixner et al, 2022).…”
Section: Nup Foci Might Not Serve An Essential Biological Role and Ar...supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, recent work has shown that sex chromosome-encoded RNA helicases such as DDX3X and DDX3Y influence the formation of RNA granules in an ATP-independent manner but have different LLPS propensities (Shen H. et al, 2022). Nuclear import of granule-associated proteins is another important layer of SG regulation (Guo et al, 2018), and defects in nucleocytoplasmic transport are a significant pathogenic factor in ALS (Zhang et al, 2015;Gleixner et al, 2022). Cytoplasmic protein clumps, which are frequently observed in many neurodegenerative illnesses, impair nucleocytoplasmic transport, implying that abnormalities in nucleocytoplasmic transport might constitute a general cause of neurodegeneration (Hutten and Dormann, 2020;Gonzalez et al, 2021;Odeh et al, 2022).…”
Section: Turnover Of Stress Granules In Health and Diseasementioning
confidence: 99%
“…We recently established a mouse model constitutively expressing an intermediate GR length, poly(GR)50, which develops mild behavioral and synaptic phenotypes (Verdone et al, 2022). While this model did not display TDP-43 mislocalization, it did show defects in the nuclear pore complex integrity, as revealed in aged mice by Nup62 mislocalization in the cytoplasm (Gleixner et al, 2022), suggesting that nuclear pore complex integrity does not univocally associate with neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%